(untitled) (International journal of artificial intelligence, 2025)
Pharmacotherapy improves survival and quality of life across acute and chronic conditions; however, all medicines may cause adverse drug reactions (ADRs). This narrative review summarizes key therapeutic benefits and the principal ADR types-predictable (dose-dependent) and idiosyncratic-outlines approach to causality assessment and risk mitigation, and highlights the importance of rational prescribing and pharmacovigilance. Balancing benefit–risk through evidence-based use, patient education, and active safety monitoring is essential to maximize outcomes and minimize harm.